Evaluation of four novel protein sources as alternatives to soybean meal for two specifications of cage-farmed grass carp (Ctenopharyngodon idellus) deeds: Effect on growth performance, flesh quality, and expressions of muscle-related genes - Fan, Ze; Li, Chenhui; Wu, Di; Li, Jinnan; Wang, Liansheng; Cao, Dingchen; Miao, Linghong; Xie, Shouqi (Frontiers in Marine Science, 2022)
We assessed the effect of total replacement of soybean meal (SBM) by Clostridium autoethanogenum protein (CAP), Tenebrio molitor meal (TMM), cottonseed protein concentrate (CPC) and chlorella powder (CHP) in diets for small specimens (initial body weight: 239.72±10.75 g) and large specimens (initial body weight: 638.32±12.64 g) of grass carp. For that purpose, five isonitrogenous (300 g/kg) and isoaliphatic (58 g/kg) diets were formulated with SBM, CAP, TMM, CPC and CHP as the only dietary protein source. Triplicate groups of fish were fed the experimental diets for 56 days. Results showed that irrespective of protein sources, large specimens of grass carp obteined the significantly reduced weight gain rate (WGR), specific growth rate, moisture, crude ash contents, drip loss rate, gene expressions of muscle S6K, MyoD and Myf-5, and the significantly increased crude protein and crude lipid contents, hardness, cohesiveness, adhesiveness, springiness, chewiness and shear force of muscles, gene expressions of muscle TOR, 4EBP1, MyoG, MRF4 and MSTN-1. Regardless of size, the CHP group possessed the markedly higher WGR, protein efficiency ratio, crude protein contents, markedly higher hardness, adhesiveness, chewiness values, gene expression levels of muscle TOR, 4EBP1, Myf-5 and MRF4, and the significantly lower feed conversion rate, drip loss rate, gene expressions of muscle S6K and MSTN-1. For small specimens or for large specimens, the essential amino-acid contents of CHP group were highest, and CHP markedly elevated the delicious amino acid and glycine contents in comparison with the SBM. Besides, CPC group also relalized the function of promoting the growth annd improving the flesh quality to a certain degree. However, total replacement of soybean meal by CAP and TMM in grass carp diets restrained the growth and damaged the flesh quality in varying degrees. Overall, comparatively, according to growth and flesh quality, chlorella powder could be a potential protein source to replace soybean meal in diets for small specimens and large specimens of grass carp.. Therefore, CHP could be a potential protein source to replace SBM in diets for use in the aquaculture of grass carp.